IFP-Based Interactive Tug-of-War Game to Improve Addition and Subtraction Learning Outcomes in Grade I - Ersa Aulia Natasya; Taufiq Khimas; Khirulnizam Abd Rahman (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2026)
This classroom action research (CAR) aimed to improve mathematics learning outcomes in addition and subtraction among Grade I students at SDN Cibilik through an Interactive Flat Panel (IFP)-based tug-of-war game. The initial assessment revealed that 15 of 27 students (55.6%) had not attained the Minimum Mastery Criterion (KKM = 70), with a class average of 67.6. The study applied the Kemmis and McTaggart CAR model across two cycles. Cycle I employed the game for C1–C2 level problems with numbers up to 10, while Cycle II incorporated three systemic improvements: a structured name-card turn-taking mechanism, C3-level problems with numbers up to 20, and mandatory five-minute collaborative review sessions after each game round. Data were collected through end-of-cycle written tests (20 items each) and structured observation sheets. Results showed consistent improvement: the class average increased from 67.6 (pre-cycle) to 74.6 (Cycle I) and 78.9 (Cycle II), while the mastery rate rose from 44.4% to 77.8% and 81.5%—surpassing the 80% success indicator. The IFP-based game effectively engaged students through instant animated feedback, team competition, and concrete visual representations aligned with the concrete operational thinking stage. This research provides evidence that the integration of game-based learning and IFP technology meaningfully advances mathematical achievement in early elementary education.